백인 교외의 ‘좋은 삶’에서 배제된 모성과 시민권: 셀레스트 잉의 『작은 불씨는 어디에나』 - 정희연(Heeyeon Jeong) (영미연구, 2025)
셀레스트 잉의 소설 작은 불씨는 어디에나 는 1990년대 말 오하이오주 셰이커 하이츠를 배경으로, 백인 중산층 교외 공동체에서 ‘좋은 삶’이라 불리는 이상이 가족, 재산, 규칙과 같은 사적 가치들과 결합하여 공동체의 공적 기준으로 작동하는 방식을 보여준다. 본 논문은 로런 벌랜트의 저작들인 미국의 여왕 워싱턴 시에 가다 , 잔인한 낙관 및 ‘시민권’에 관한 논의를 중심으로, 감정과 애착이 시민의 자격을 구성하고 공동체 내부에서 정서적 기준이 되는 방식을 살핀다. 리처드슨 부인이 체현하는 규범적 모성은 ‘좋은 삶’에 대한 정동적 애착과 맞물리며, 공동체의 타자에 대한 선별적 수용과 배제를 낳는다. 특히 아시아계 아동의 양육권 소송은 ‘좋은 어머니’와 ‘미래의 시민’이라는 관념이 인종과 계급에 따라 다르게 해석되는 현실을 드러낸다. 이 논문은 작품에 나타난 정동과 친밀성의 정치가 어떻게 공적 질서를 형성하고 유지하는지를 비판적으로 추적하며, 문학 텍스트가 감정 정치와의 교차점으로 기능할 수 있음을 보여주고자 한다. Celeste Ng’s Little Fires Everywhere takes place in Shaker Heights, Ohio, in the late 1990s, and closely examines issues of family, community, race, and class. This paper focuses on Elena Richardson, a white middle-class woman who believes strongly in rules, order, and what she perceives as a ‘good life.’ It explores how her beliefs shape the way she judges others and tries to control the world around her. Drawing on Lauren Berlant’s theories of citizenship and cruel optimism, the paper looks at how Richardson’s sense of right and wrong allows some people to belong while pushing others out. The paper also analyzes the custody battle over an Asian American baby, showing how ideals of good motherhood and citizenship often depend on race and class. Through these stories, Little Fires Everywhere reveals who gets included in the promise of a good life—and who is left out. The novel illustrates how private lives and public values were deeply connected in shaping the imagined future of American society. This paper reads Little Fires Everywhere as a critical reflection on how ideals of the good life were maintained, negotiated, and enforced in late twentieth-century suburban America.. KCI Citation Count: 0